World Bank Research Digest, Vol. 3(4) - World Bank (Washington, DC, 2014)
In this issue: trade and the current crisis; viewpoint: back to global imbalances? Impact assessments in finance and private sector development; why don't we see poverty convergence? Sovereign rents and quality of tax policy and administration; globalization and international capital raisings; and climate change deepens vulnerability to poverty.